2006
DOI: 10.1209/epl/i2005-10526-y
|View full text |Cite
|
Sign up to set email alerts
|

Granular temperature distribution in a gas fluidized bed of hollow microparticles prior to onset of bubbling

Abstract: It has been unclear whether bubbles are required to induce particle velocity fluctuations in gas fluidized beds (FBs). We show that bubbles are not necessary by applying diffusing-wave spectroscopy to particles whose minimum bubbling velocity is approximately 5 times that of the minimum fluidization velocity. Fluctuations are first observed at or just above fluidization and increase in magnitude with superficial velocity. The distribution of velocity fluctuations in the bed is also presented: they are symmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…9 shows variation of height-averaged velocity fluctuations with superficial velocity. The velocity fluctuations are the same order of magnitude as the driving velocity as observed in the other FB systems considered by us to date (Xie et al, 2006;Biggs et al, 2008a,b;Zivkovic et al, 2008), and increase with superficial velocity up to a maximum at U 0 = 7.5 mm/s. Batchelor (1988) hypothesized that for a uniform FB, the particle velocity fluctuations can be related to the mean particle velocity averaged over the FB cross-section, v, by where H() is a function of the solid fraction only.…”
Section: Spatial Variation Of Granular Temperaturesupporting
confidence: 81%
See 2 more Smart Citations
“…9 shows variation of height-averaged velocity fluctuations with superficial velocity. The velocity fluctuations are the same order of magnitude as the driving velocity as observed in the other FB systems considered by us to date (Xie et al, 2006;Biggs et al, 2008a,b;Zivkovic et al, 2008), and increase with superficial velocity up to a maximum at U 0 = 7.5 mm/s. Batchelor (1988) hypothesized that for a uniform FB, the particle velocity fluctuations can be related to the mean particle velocity averaged over the FB cross-section, v, by where H() is a function of the solid fraction only.…”
Section: Spatial Variation Of Granular Temperaturesupporting
confidence: 81%
“…DWS (Weitz and Pine, 1993), which has now been applied extensively in the study of particle dynamics in various dense granular systems (Menon and Durian, 1997a,b;Xie et al, 2006;Biggs et al, 2008a,b;Zivkovic et al, 2008) was used here in the transmission mode as illustrated in Fig. 1b.…”
Section: Diffusing Wave Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Menon and Durian, 1997). Diffusing wave spectroscopy (DWS) has demonstrated that spatial variations in the granular temperature in a two-dimensional gas-fl uidised bed are signifi cant and cannot be ignored (Xie et al, 2006). Positron emission particle tracking (PEPT) has been used to track the velocity and fl uctuations of a single radioactive tracer particle in a dense, three-dimensional system (Wildman et al, 2001).…”
Section: Experimental Determination Of Granular Temperaturementioning
confidence: 99%
“…They found that the granular temperature in the axial direction is larger than that in the lateral direction. Xie et al (2006) used a diffusing wave spectroscopy (DWS) to measure the displacement of glass beads in a fluidized bed, and demonstrated that the spatial variations in the granular temperature are significant in a fluidized bed. Holland et al (2008) and Muller et al (2008) measured particle motion in the bubbling fluidized bed by a magnetic resonance technique (MR).…”
mentioning
confidence: 99%